2022
DOI: 10.3390/jcm11164861
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease Guidelines for Corneal Refractive Surgery Evaluation

Abstract: Inflammatory bowel disease (IBD) is a chronic systemic inflammatory condition that can potentially adversely affect surgical outcomes in patients receiving elective ophthalmic procedures. In this case series, 21 eyes of 11 patients with ulcerative colitis or Crohn’s disease underwent laser in situ keratomileusis (LASIK), photorefractive keratectomy (PRK), or small incision lenticule extraction (SMILE). Their surgical outcomes were followed up for an average of 8.9 ± 4.6 months. All the patients in this study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Dry eye symptoms are also not uncommon in these patients due to fat-soluble vitamin deficiencies. The LVC is relatively contraindicated in IBD [3,9,16]. The LASIK surgery is relatively possible in well controlled stage of the disease, while in exacerbation of the IBD, the immune response may result in unfortunate complications such as necrotizing keratitis [16,17].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Dry eye symptoms are also not uncommon in these patients due to fat-soluble vitamin deficiencies. The LVC is relatively contraindicated in IBD [3,9,16]. The LASIK surgery is relatively possible in well controlled stage of the disease, while in exacerbation of the IBD, the immune response may result in unfortunate complications such as necrotizing keratitis [16,17].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…The LVC is relatively contraindicated in IBD [3,9,16]. The LASIK surgery is relatively possible in well controlled stage of the disease, while in exacerbation of the IBD, the immune response may result in unfortunate complications such as necrotizing keratitis [16,17]. Immunomodulating medication use, in the management of IBD, such as azathioprine, tacrolimus and methotrexate does not constitute a contraindication for LVC.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…However, immunotherapy still faces significant challenges, including long-acting immune stimulation impediment [12] and inflammatory irritation after surgery. [13] Researchers often focus on reshaping the tumor microenvironment (TME) [14] to boost the immune response to balance the complexity between malignant cells and the immune defense system. [15] Emerging evidence has indicated that pyroptosis [16] could reactivate the immune system and enhance tumor immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…However, immunotherapy still faces significant challenges, including long‐acting immune stimulation impediment [ 12 ] and inflammatory irritation after surgery. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%